Developing a Quality Culture:Case Study - Sallis, Edward (Journal of Engineering Education Transformations, 2006)
This is a case study of how a college developed its own quality framework. It charts the progress since 1998 when the College started on the journey to self-improvement, which is its name for total quality management. An important feature of the programme is that it is a self-generated model, broadly following the principles of total quality management and similar models of continuous improvement. The programme has grown into a complex and rich institutional quality improvement process that has led to high student retention and achievement, and is providing considerable bench marking data for further improvement. It has lessons for the development of quality systems ill institutions of higher educational.